PONV (Postoperative Nausea and Vomiting) Incidence among Patients with Caesarean Section, Enhanced Recovery After Surgery (ERAS), and Subarachnoid Block (SAB) Anesthesia - Yustina Ni Putu Yusniawati; Emanuel Ileatan Lewar; I Gde Agus Shuarsedana; Valentine Claradicha (Babali Nursing Research, 2023)
Background, ERAS has been widely demonstrated as an effective method for controlling postoperative pain, nausea, and vomiting. Pain management that cuts the dose of opioids by 50%, involves administering intravenous fluids, and using a combination of antiemetic drugs may have a better outcome. objective. This study aims to determine the incidence of PONV after the ERAS procedure in cesarean section patients with Subarachnoid Block (SAB) anesthesia. Method, This research is quantitative research with a descriptive design. This study was conducted from March to April 2022, involving 60 post-cesarean section patients with SAB and ERAS. Univariate analysis that presents the frequency distribution of PONV events was applied to answer the research objectives. Results, Most of the participants were between 30 and 35 years old (29; 48.3%), classified into the healthy weight group (33; 55%), and identified with a Bromage score of 1 (60; 100%). The majority of participants amounting to Fifty participants (83.3%) did not experience episodes of nausea and vomiting after the procedure. Only seven (11.7%) and three (5%) participants reported mild and moderate nausea and vomiting after the process, respectively. Conclusion, the ERAS method is an adequate technique presented in cesarean section procedures. The findings confirm its effectiveness in reducing the incidence of postoperative nausea and vomiting. Thus, proposing ERAS as an effective and promising protocol for cesarean section procedures.